Improving the pasture quality through the annual legumes oversowing: previous results on the seed bank response - Franca A.; Seddaiu G. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
The understanding of changes in botanical composition and seed bank dynamics was the aim of an experiment conducted on a natural pasture and oversown with annual ryegrass, subclover and burr medic. The site is located in western Sardinia and was grazed at 8 ewes per ha per year in April, September and December. Viable seed bank (VSB) composition was assessed by collecting intact soil cores at the end of summer 1998. VSB pool components were separated by 3 germination per dormancy breakdown treatments, thus estimating germinable (GSB) and dormant (DSB) seed bank. Autumn and spring overlying vegetation was estimated by non-destructive method using an HFRO sward stick, by recording 4 specific leaf contacts at the vertices of 1200 random quadrats (20 x 20 cm). Changes in overlying vegetation and VSB were analyzed after the durnig the first year after the oversowing: 15 per cent of the VSB was represented by Trikkala subclover which contributed with almost all the seeds as readily germinable.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)